Mengatasi Kesenjangan Teknologi di UMKM: Studi Pengabdian Masyarakat dengan Digital Marketing dan HRM Inovatif - Mukhlison Suryanto; Roihatul Mawadah; Harini Abrilia Setyawati (PT. Alahyan Publisher Sukabumi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy but still face significant technological gaps, especially in rural areas. In the era of Industry 4.0, adapting to technology is essential to enhance competitiveness. This community service program aimed to address technological disparities in the MSME group of Bocor Village, Kebumen, through training in digital marketing and innovative Human Resource Management (HRM). The activity used a Participatory Action Research (PAR) approach, engaging MSME actors in three stages: problem identification through surveys and focus group discussions, training on WhatsApp Business, Instagram marketing, and innovative HRM, followed by one-month mentoring and performance evaluation. The results showed a notable improvement in digital literacy: 90% of participants successfully adopted WhatsApp Business, and over 70% began actively using Instagram for marketing. The HRM strategies fostered team collaboration and operational efficiency. Participants experienced a 15% average increase in revenue within one month. This program demonstrated that a combination of digital marketing and innovative HRM is effective in overcoming technological gaps and can serve as a replicable model for MSME development in other regions.